Pengaruh penerapan model discovery based learning terhadap pencapaian hasil belajar fisika siswa kelas X SMA - Indri Shovyana Putri; Amali Putra (Universitas Negeri Padang, 2019)
There are several factors that affected to the low learning outcomes of student, such as the learning models, learning motivation, and student worksheets used which were still very simple. This research aims to determine the effect of applying the discovery based learning model to the learning outcomes of class X students. Sampling was done by using purposive sampling technique obtained by class X MIA 1 as the experimental class and class X MIA 2 as the control class. There are two data collected, namely primary and secondary data. The primary data in this study were the final test results at the end of the lesson. Secondary data in this study were in the form of midterm average scores obtained from teachers and Physics administration. The data obtained was processed using the t test and correlation test. According to the results of the analysis of the data found the results of the influence of the implementation of the discovery based learning model on the knowledge aspect of 20.25% and for the skills aspect has an effect of 26% on physics learning so that the hypothesis was accepted with α significant = 0,05.